Lone wolf terrorism: understanding the growing threat - Simon, Jeffrey D. (Prometheus Books, 2013)
Essential reading for anyone concerned about the potential terrorist threats from violence-prone individuals in our midst. Lone wolves have demonstrated that they can be as dangerous as organized terrorist groups. Who are these terrorists and what can be done about them?